2015
DOI: 10.3748/wjg.v21.i45.12896
|View full text |Cite
|
Sign up to set email alerts
|

Possible association between hepatitis C virus and malignancies different from hepatocellular carcinoma: A systematic review

Abstract: To date no definitive conclusions may be obtained from the analysis of relationship between HCV and extra-hepatic cancers. Further studies, recruiting an adequate number of patients are required to confirm or deny this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 237 publications
0
58
0
7
Order By: Relevance
“…Unlike other studies, we only observed a higher risk of hematological malignancies and oral cancers in HCV patients. Different hypotheses can be advanced regarding these two types of cancer: a direct impact of viral replication in the case of lymphoid and related tissue cancers and a potential role for other cancer risk factors such as metabolic syndrome and chronic tobacco and alcohol intake in the case of oral cancer.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Unlike other studies, we only observed a higher risk of hematological malignancies and oral cancers in HCV patients. Different hypotheses can be advanced regarding these two types of cancer: a direct impact of viral replication in the case of lymphoid and related tissue cancers and a potential role for other cancer risk factors such as metabolic syndrome and chronic tobacco and alcohol intake in the case of oral cancer.…”
Section: Discussionmentioning
confidence: 62%
“…In terms of solid tissue cancers and more particularly smoking‐related cancers (pancreas, rectum, kidney, and lung), our results differed from those of previous studies . As described in the literature on HCV patients, we observed a higher age‐adjusted incidence of oral cancers (SMR, 2.96; 95% CI, 1.42‐5.45; P = 0.005); but this risk disappeared after account was taken of confounding factors such as tobacco and alcohol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Therefore, HCV infection promoting diabetes might act in cooperation with hyperinsulinemia, hyperglycemia in the promotion of pancreatic cancer. 19 The prevalence of HCV antibody in Egypt in 2015 was found to be 10% and that of HCV RNA to be 7% in the age groups 15-59 year. 20 Although, the high prevalence of HCV infection, pancreatic cancer is not common in Egypt.…”
Section: Resultsmentioning
confidence: 98%
“…During this time, the virus can cause liver scarring, potentially leading to cirrhosis, liver cancer and liver failure [44]. HCV, along with Hepatitis B, has also been tenuously linked with pancreatic cancer and leukaemia/lymphoma [45][46][47]. The targeting of XRN1 by these viruses indicates that XRN1 is normally vitally important in protecting the cell from these viral pathogens.…”
Section: Xrn1 and The Host Response To Virusesmentioning
confidence: 99%